Gamification of cooperation: A framework, literature review and future research agenda - Riar, Marc; Morschheuser, Benedikt; Zarnekow, Rüdiger; Hamari, Juho (International Journal of Information Management, 2022)
Cooperation is in many ways a meaningful behavior and understanding how cooperation can be fostered among humans is integral to solving the many global challenges we are facing. Thus, one of the major current developments exists in exploring the potential of gamification to engage people in cooperative activity. However, while the literature on this phenomenon is growing in numbers, it remains unclear how gamification motivates cooperation and how effective it is in cooperative settings. This lack of understanding obstructs us from designing gamification that appropriately supports cooperation and from comprehending what potential hurdles need to be considered. We close this gap by theorizing a framework for gamifying cooperation. Guided by this framework, we systematically review and synthesize the existing literature (n = 51) to understand how gamification has been previously employed to motivate cooperation and what is known about the effects of gamification in cooperative contexts. The main contribution of the present study consists in deducing three different approaches (i.e., based on individualistic, cooperative, and hybrid use of features) to motivate cooperation by gamification and in providing a strategic platform for future research by proposing 11 agenda points regarding thematic, theoretical, and methodological future research avenues for gamifying cooperative activity.<br
Keywords: Gamification; Cooperation; Collaboration; Teamwork; Literature review; Design